Organized Cohabitation and Domestic Hyper-proximity in Social Policies - Costa, Giuliana (Italian Sociological Review, 2022)
This article focuses on a specific ingredient of social and care policies with a housing dimension, namely, organized cohabitation among unrelated users. The topic is little explored, both by the social sciences, by those involved in the analysis of public policies, and by those disciplines that look more closely at the dimensions of space. Hyper-proximity in domestic spaces is an issue that concerns many social groups and social needs. In fact, there are several social services and projects that target coexistence “under the same roof and behind the same door” (Costa, 2015a; 2020) as a fundamental pillar of their action. Sharing domestic spaces in welfare interventions allows to reduce costs, to better organize professional work and to implement individualized programs that possibly make day by day sharing - of experiences, of ways of doing and being, of facing problems - a strength. I propose some key dimensions for analyzing this specific form of life which concerns people who, for different reasons, find themselves facing complex and intersectional problems. The article presents some findings of a research devoted to study different cohabitation projects and services around Italy, developed through 42 interviews to key informants, such as policy makers, services managers, services coordinators, professionals, to understand if and how these cohabitation solutions succeed in coping with the intersectional problems of the users.